Gaming the gamers : using experience maps to develop revenue-generating insights - Grayson, Kent; Waikar, Sachin; Smith, Gene ([London] : SAGE, 2016)
A senior product manager for a telecommunications company has been asked to propose ideas for generating new revenue from video gamers who use his company's Internet services. The manager has commissioned the development of 'experience maps' for three subsegments within the gamer segment. The experience maps, which are reproduced in the case, provide students with an opportunity to generate customer insights based on real qualitative data.
Originally Published in: Grayson, K., & Waikar, S. (2012). Gaming the Gamers: Using Experience Maps to Develop Revenue-Generating Insights. 5-212-250. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Marketing research -- Case studies; New products -- Case studies; Product management -- Case studies